China's higher education reform and internationalisation - Ryan, Janette, 1956- (Routledge contemporary China series, 2011)
Despite radical and fundamental reform of the Chinese higher education system, very little is known about this outside China. The past decade has seen radical reform of all levels of China's education system as it attempts to meet changing economic and social needs and aspirations: this has included transformation of university curricula, pedagogy and evaluation measures, rapidly increasing joint research and degree programmes between Chinese universities and universities abroad, and very large numbers of Chinese students studying at universities outside China. This book describes the historica.